Prevalence of Severe Anemia among Pregnant Females and Factors Associated With Anemia in Pregnancy - Amna Najam, Shamim Akhtar, Amreen Khan, Umber Fatima, Samreen Fakeer Muhammad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: According to World health organization anemia is most common among females during pregnancy and child birth. Maternal and fetal morbidity and mortality is high due to anemia in pregnancy as it is a contributing factor in poor pregnancy outcome. It is the main cause of maternal death, almost 29% of women die due to anemia in pregnancy. Half of the maternal mortality causes are related to anemia in pregnancy either directly or indirectly. What so ever is the cause of anemia in pregnancy, its management is important for mother and child health. The consequences of anemia have serious health implications especially among pregnant females. Methodology: The cross-sectional study was conducted to find prevalence of anemia during first, second and third trimester of pregnancy and factors related to cause of anemia. A total of 340 pregnant females of government and private hospitals of Lahore city during the period from February 2017 to August 2018 were included in study after sample size calculation through convenient sampling. Sociodemographic, economic status, education level, number of children born to females and gestational period were the factors that were studied among anemic pregnant females. Data analysis was done and frequencies of continuous variables and descriptive analysis for categorical variables were determined. Prevalence of anemia was determined by multinomial logistic regression. Results: Our study showed females were with mean age 27.9 (±SD=5.4) and in age group 31-39 years (53.8%) were more anemic during pregnancy as compared to females <30 years of age. Most of the females (67.1%) were housewives and had primary level of education (49.1%). Among these females (30%) were with mild anemia, (53.5%) were with moderate anemia and (16.5%) were with severe anemia. The mean hemoglobin level was 9.8g/dl (SD=±1.6). Among pregnant females 152(45%) were anemic during third trimester of pregnancy. Result showed 167(48.8%) females were anemic having children > 3. Sociodemographic factors, education level, number of children born to female, economic status all were significantly associated with moderate anemia during pregnancy (p=0.00). Conclusion: Our study showed that although the prevalence of anemia is more among pregnant females but the severe anemia was less. So, it is a preventable health problem which can be controlled by different public health approaches to reduce the burden of disease on the health system. The strategies to control anemia in reproductive age women is important to prevent it among pregnant women. the early diagnosis and immediate correction of anemia is important to reduce the complications of pregnancy and its poor outcome. Early identification of factors is significantly important in managing the problem. Keywords: anemia, pregnancy, prevalence of anemia, gestational period.